A Content analysis of the reportage of the Laiban Dam Project in the Philippine Daily Inquirer, the Philippine Star, and the Manila Bulletin - Sun, Cherry Elaine Joyce Evangelista (Quezon City College of Mass Communication, University of the Philippines Diliman, 2011)
"The Philippines has a long history of press manipulation as the print media has become a business enterprise. External powers like businesses have put extra-legal limitations on the media. This thesis examined the potential role of the private sector in influencing the agenda-setting function of the Philippine Daily Inquirer, The Philippine Star and the Manila Bulletin in their reportage of the Laiban Dam project. This study attempted to check the performance of the three leading national broadsheets in reporting the Laiban Dam issue in adherence to its Agenda-setting and Framing functions, to gauge the private sector's influence on the press in relation to the Critical Media theories and to identify lapses and, consequently, improvements in the practice of journalism. The researcher analyzed a total of 126 matches published in the aforementioned broadsheets from February 10, 2009 to September 10, 2010 and interviewed a media expert for the validation of the initial findings. The treatment of the issue by the Philippine Daily Inquirer, the Philippine Star and the Manila Bulletin as a business agenda confirmed the possible precedence of external powers over the power of the media."
Thesis (A.B. Journalism)--University of the Philippines Diliman